Creating a corporations law case study - Bruce Dyer; Mary-Anne Hughson; Sam Ricketson (Legal Education Review)
The following paper draws on the experience of the Monash Law School in preparing a case study based on an actual court decision for use in teaching Corporations and Business Associations Law. This is the basic corporate law subject which is done by all law students at Monash as part of their LLB degree. As its name suggests, Corporations and Business Associations Law also deals with non-corporate forms of business association, in particular the partnership. Nonetheless, the primary focus of the subject is the corporation, and its place and role within Australia.